Supplier Network Intelligence Collection Framework - Jeeva, Ananda; Zhu, Dengya (Maastricht University, 2011)
This paper proposes the use of an integrated information retrieval framework (IIRF) to facilitate the collection of critical information of a manufacturer’s supply network. It explores the requirements for a sustainable survival of manufacturers by aligning information among the entities within a supply network. It proposes that manufacturers must have accurate and current information and data of their prime suppliers of critical components. Current research and literature search indicates there are very little publications investigating supplier intelligence in the context of the supply network like suppliers’ supplier’s financial health in terms of capital investment, debt, market performance, financial reporting, accounting practices, corporate governance, competitive factors and operating environment. This paper proposes a data gathering model for collating supplier intelligence from the internet and commonly available online sources. The impetus for such information is becoming more critical in a supply network. Supplier intelligence enables long term procurement strategies with greater certainty.